Problem Guantánama - varstvo ustavnih pravic za bodečo žico - Zagorac, Dean (Revus (Ljubljana), 2004)
The US military base at Guantanamo, Cuba, where since January 2002 the military has been detaining alleged terrorist for the purpose of escaping habeas corpus jurisdiction of the US courts, has become a symbol of arbitrariness and cruelty of the US authorities. The situation raises the following questions: what status should the detainees have; under which corpus of law are they protected; and can the executive branch hold them in detention and try them without the possibility of review by regular courts. The author, through presenting the international legal status of the territory, over and within which the US exercises "complete jurisdiction and control" and Cuba retains "ultimate sovereignty", and the relevant jurisprudence presents the reader with dimensions of the third question. The author indicates which dilemmas will need to be addressed by the US Supreme Court when it issues an opinion in July 2004 on whether the detainees from Guantanamo have a right to judicial review of their detention.
Keywords: človekove pravice; humanitarno pravo; mednarodno pravo; odvzem prostosti; pravno varstvo; taborišča; terorizem; ujetniki; ustavno pravo; vojaška taborišča; ZDA